Gamma Knife Radiosurgery after Stereotactic Aspiration for Large Cystic Brain Metastases - Park, Won Hyoung (The Korean Neurosurgical Society, 2009)
OBJECTIVE: Several treatment options have proven effective for metastatic brain tumors, including surgery and stereotactic radiosurgery. Tumors with cystic components, however, are difficult to treat using a single method. We retrospectively assessed the outcome and efficacy of gamma knife radiosurgery (GKRS) for cystic brain metastases after stereotactic aspiration of cystic components to decrease the tumor volume. METHODS: The study population consisted of 24 patients (13 males, 11 females; mean age, 58.3 years) with cystic metastatic brain tumors treated from January 2002 to August 2008. Non-small cell lung cancer was the most common primary origin. After Leksell stereotactic frame was positioned on each patient, magnetic resonance images (MRI)-guided stereotactic cyst aspiration and GKRS were performed (mean prescription dose : 20.2 Gy). After treatment, patients were evaluated by MRI every 3 or 4 months. RESULTS: After treatment, 13 patients (54.2%) demonstrated tumor control, 5 patients (20.8%) showed local tumor progression, and 6 patients (25.0%) showed remote progression. Mean follow-up duration was 13.1 months. During this period, 10 patients (41.7%) died, but only 1 patient (4.2%) died from brain metastases. The overall median survival after these procedures was 17.8 months. CONCLUSION: These results support the usefulness of GKRS after stereotactic cyst aspiration in patients with large cystic brain metastases. This method is especially effective for the patients whose general condition is very poor for general anesthesia and those with metastatic brain tumors located in eloquent areas.